New spectroscopic data for atomic tungsten XIV - Raineri, María Mónica (2014)
The thirteen times ionized tungsten is isoelectronic with PmI. Wavelengths and transition probabilities for the 5s-5p and 5p-5d transitions of WXIV, identifying the ground state as 4f13 5s2 2F7/2 were calculated. Both, a relativistic Hartree Fock approach, including core-polarization effects, and a purely relativistic multiconfiguration Dirac-Fock method were used for the calculations. Particularly, 5s-5p transitions were compared with experimental results obtained with VUV electron beam ion trap (EBIT) spectroscopy.